The Germans and the Holocaust : popular responses to the persecution and murder of the Jews - Schrafstetter, Susanna; Steinweis, Alan E. (Vermont studies on Nazi Germany and the Holocaust., 2015)
For decades, historians have debated how and to what extent the Holocaust penetrated the German national consciousness between 1933 and 1945. How much did "ordinary" Germans know about the subjugation and mass murder of the Jews, when did they know it, and how did they respond collectively and as individuals? This compact volume brings together six historical investigations into the subject from leading scholars employing newly accessible and previously underexploited evidence. Ranging from the roots of popular anti-Semitism to the complex motivations of Germans who hid Jews, these studies illuminate some of the most difficult questions in Holocaust historiography, supplemented with an array of fascinating primary source materials.